Bioethanol production using the SSF method (simultaneous saccharification and fermentation) of microalgae anabaena sp. (April 2020) - Permatasari, N S; Zainuri, M; Kusumaningrum, H P; Mishbach, I; Hastuti, E D
Abstract: Bioethanol is one of the alternative energy sources that answer the current energy crisis problems. The advantage of bioethanol compared to the fuel oil (BBM) is biodegradable. It contains an octane and high oxygen so it is flammable and reducing global warming emissions. Recently, the main ingredient of bioethanol has entered the third generation which is using microalgae. Anabaena sp. is one of the microalgae types from cyanobacteria which has the advantage of being used as bioethanol because it has carbohydrate biomass of about 20-30%. This research is aimed to produce bioethanol from microalgae Anabaena sp. The bioethanol production method used SSF because the advantage showed the converted polysaccharides into monosaccharides did not return to polysaccharides. It was caused monosaccharides directly fermented into ethanol. The use of one reactor reduced the cost of the process in the equipment used. This research was conducted in several stages, namely the preparation of raw materials, acid hydrolysis using H2 SO4 1 M, and fermentation with the help of Saccharomyces cerevisiae microorganisms anaerobically. The results showed that using the SSF method was able to produce ethanol levels of 7%.